Python for Data Science and Machine Learning Essential Training Part 1. - Pierson, P.E., Lillian (linkedin.com, 2024)
Learn Python programming skills for data science and machine learning. Discover how to clean, transform, analyze, and visualize data, as you build a practical, real-world project.